The Effect of Mamakiah Tradition toward Students' Education in Padang Pariaman Traditional Islamic Boarding School - Edriagus Saputra; Samiullah Taraki; Nana Gustianda; Zakiyah Zakiyah (FOKUS Jurnal Kajian Keislaman dan Kemasyarakatan, 2022)
The tradition of Mamakiah is a form of habit that students from generation carry out to generation to support and assist their lives in carrying out education at Islamic Boarding Schools in the Padang Pariaman area. However, the community sees this tradition as a habit that is equated with beggars and begging. This study uses a descriptive qualitative model to use a field research method (field research). The result of this study is that the mamakiah tradition carried out by the students of the Padang Pariaman Traditional Islamic Boarding School is a form of learning provided by the Pondok to help the cost of living and education students while at the Islamic Boarding School. In addition, this tradition also provides education to students related to Education of Patience, Sincerity, helping each other and providing opportunities for the community to give alms.